2021
DOI: 10.1523/jneurosci.2539-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Selective Ablation of BDNF from Microglia Reveals Novel Roles in Self-Renewal and Hippocampal Neurogenesis

Abstract: Microglia, the resident immune cells of the CNS, have emerged as key regulators of neural precursor cell activity in the adult brain. However, the microglia-derived factors that mediate these effects remain largely unknown. In the present study, we investigated a role for microglial brain-derived neurotrophic factor (BDNF), a neurotrophic factor with well known effects on neuronal survival and plasticity. Surprisingly, we found that selective genetic ablation of BDNF from microglia increased the production of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 64 publications
(76 reference statements)
0
20
0
Order By: Relevance
“…In agreement with our results, it has been shown that repeated administration of cocaine leads to a reduction of this neurotrophic factor in the hippocampus 78 , 79 . Although microglia may not represent the main source of BDNF in the brain, the release of this neurotrophin by these cells seems to be important in physiological and pathological conditions 80 . In addition, it has been shown that BDNF synthesis and release are regulated by a plethora of events and circumstances, such as altered levels of ions, depolarization, neurotransmitters, hormones, inflammatory mediators, among others 81 .…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, it has been shown that repeated administration of cocaine leads to a reduction of this neurotrophic factor in the hippocampus 78 , 79 . Although microglia may not represent the main source of BDNF in the brain, the release of this neurotrophin by these cells seems to be important in physiological and pathological conditions 80 . In addition, it has been shown that BDNF synthesis and release are regulated by a plethora of events and circumstances, such as altered levels of ions, depolarization, neurotransmitters, hormones, inflammatory mediators, among others 81 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, microglia provide trophic support to their neighboring cells by secreting neurotrophic factors, including nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), fibroblast growth factor (FGF) and Insulin-like Growth Factor (IGF), thereby regulating neuronal function and synapse formation [ 29 , 43 , 44 ]. In turn, NGF and BDNF can regulate microglial functions [ 13 , 14 , 45 , 46 , 47 , 48 ].…”
Section: Microglia In Health and Neurodegenerative Diseasementioning
confidence: 99%
“…Microglia are the brain-resident innate immune cells with increasingly recognized roles in neuronal function and brain homeostasis, which includes the control of the neurogenic niche in the adult hippocampus [ 417 ]. Microglia have been shown to be a relevant cellular component part of the neurogenic niche [ 418 ] and to physiologically regulate hippocampal adult neurogenesis at multiple steps of the neurogenesis process, using phagocytosis secretome [ 419 , 420 ], signaling through the CX3C-receptor-1 (CX3CR1) [ 421 , 422 ], and the release of BDNF [ 423 ]. In addition, experiments of microglia ablation suggest that microglia are required for basal hippocampal neurogenesis [ 424 ].…”
Section: Mechanisms Of Stress Acting On Neurogenesismentioning
confidence: 99%